Development instrument science process skills biology for Junior High School - Rifda Tanfiziyah; Budhi Akbar; Devi Anugrah (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2021)
Science process skills (SPS) are basic skills in science and tools of a scientist to investigate science phenomena. One of the ways to improve science process skills is by giving students practice questions. This study aims to develop a valid and reliable science process skills instrument. The research is developmental research using a procedural model adapted from Djaali and Muljono. These steps include the theory synthesis stage, the design stage (variable construction, development of question indicators, preparation of grids, making instruments, scoring), and the evaluation stage (validity test, reliability test, and item analysis). The research instruments used were expert validation sheets, practitioner assessment questionnaires, and product trial questions for 100 students. The results of judgment expert and practitioner judgment were processed descriptively. The empirical validity results, which are quantitative data, are processed using the software Microsoft Excel. The results showed that the developed questions were valid based on logical validity (89.43%) and empirical validity (84%). The reliability calculation shows the high category (0.66). This study concludes that the SPS questions developed are feasible to assess the process skills of biology subjects at the junior high school level.